A study on the online resources cited in the theses and special problems done at the University of the Philippines School of Library and Information Studies - Honrade, Lorraine Dawn G.; Aguirre, Vyva Victoria M. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2008)
The Internet is a unique medium in which information is published. With the increase of its popularity as information source is a concern about the preservation of its content. It is in this light that the study is focused on the online resources cited in the theses and special problems done at the University of the Philippines-Diliman School of Library and Information Studies. Four hundred ninety-seven theses and special problems were studied.
The data gathered revealed that (a) books are the most popular sources of information accounting for the 37.91 percent of all the materials cited; (b) there is an increasing trend of citing online materials through the years; (c) the proportions of online resources over other formats increase through the years; (d) a total of 2401 online resources were cited; (e) the most cited link is http://nlm.nih.gov/mesh/, and the most frequented domain in which cited links were accessed is www.ifla.org; (f) 60.64 percent of the links cited are still accessible and the percentage of accessible links over those that are no longer accessible increases each year both for the bachelor's and master's degrees; (g) the most common errors received are "file/page not found" and "domain error"; (h) the most common type of website visited is commercial websites (.com) based on the top-level domain; and (i) more recently accessed links have higher probability of still being retrieved.
For further study, it is recommended to investigate the reasons for the disappearance of the cited pages. Also, it will be worthwhile to look into other fields to determine if the trends are similar.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines. School of Library and Information Studies -- College students; University of the Philippines. School of Library and Information Studies -- Graduate students; Citation of electronic information resources -- Philippines -- Quezon City